Crônica de humor : objeto de ensino-aprendizagem na perspectiva do interacinismo sociodiscursivo - Santana, Catiana Santos Correia (2016)
This study aims to analyze the chronic gender humoristic from the perspective of Interacionism Sociodiscursive (ISD) of Bronckart ([1999] 2012), trying to understand how the categories of discursive world defined in theoretical proposal ISD help interpret and understand the chronic humorous classroom. Drawing on the notion of chronic humorous genre is defined such text as episodic story that deals with political events or customs of everyday life. Therefore, such texts promote a humorous criticism of social behavior patterns and worldviews established in a certain historical period of polyphonic manner, thus bringing controversial issues to / from social universe. In order to understand how critical are manifested in this kind of discourse, we assume that the production of meaning depends on the finding of intertextual relations, configurational understanding between types of speech, observing the voices of the game and understanding of way of functioning of discourse manifested worlds of implied and autonomously within the chronic. Explicitaremos these discursive relations, from a thematic point of view. This analysis aims at drawing up a pedagogical notebook reading to work the linguageiras capabilities within the chronic, highlighting how teachable understanding of the effect of humor. The methodology is underlies the case study and treatment of the data was done by examining the activities carried out by Sanchez methodology (2016) and Machado (2009), the experience report.